PERAN GURU DALAM PENANAMAN NILAI-NILAI 7K - Muhammad Arizal; Izhar Salim; Maria Ulfa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the role of teachers in instilling 7k ( faith, security, orderliness, cleanliness, beauty, shade, family) in SMPN 21 Pontianak. A common problem in this study was how the role of the teacher in planting a value of 7k in SMPN 21 Pontianak. The problems in this study are: 1) how the role of the teacher as an example in planting a value of 7k in SMPN 21 Pontianak. 2) how the role of the teacher as an motivator in planting 7k in SMPN 21 Pontianak. 3) how the role of teacher  as an supervisor in planting 7k in SMPN 21 Pontianak. This study aimed to describe the role of teacher in planting 7k in SMPN 21 Pontianak. The method used was a qualitative method with descriptive analysis. The data collection tool used observation guides, interview guides and with documentation tools. From the results of the research that has been done, it can be concluded that the role of the teacher in planting 7k grades in SMPN 21 Pontianak is still not going well. Based on the results of the study shows that there are still a number of 7k programs that are still not well implemented by students such as: 1) security where there are still students carrying items that are prohibited by schools such as (cellphones, make up and jewelry). 2) orderliness seen that there are still students who still do not complete the attributes and arrive late at school. 3) cleanliness seen there are still students who throw rubbish in the school environment and in the class room.        Keyword:  Teacher’r Role, Value of 7K